If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2z+33=17
We simplify the equation to the form, which is simple to understand
2z+33=17
We move all terms containing z to the left and all other terms to the right.
+2z=+17-33
We simplify left and right side of the equation.
+2z=-16
We divide both sides of the equation by 2 to get z.
z=-8
| 26y-12=18y+12 | | 6(c-4)=3(s+9) | | 2b+9=188 | | 4(4x-4)+40=9x+3 | | 40.06=8g+3.58 | | 8(5y-3)3.2=x | | -4=-8n+8n | | 45+9x=-14 | | 3x^2(4x+5)= | | 17x+66+11x=-1+x | | 10*.5+8=5*.5+3+3(.5+2) | | -7(9a-4b)= | | 15x+5=-5 | | -3(-n-8)-2(8n+6)=n-8n | | 12y^3-16y^2+4y=0 | | 18a+21= | | (3x-22)=80+x | | 3x+5-2=11-8 | | 8(5x-3)3.2=y | | -(-93)= | | 2x(9-x)= | | 8(n+8)=-8(-5n+1)+4n | | 27m-7m=40 | | 15x=3y+6 | | 8y-62=-y-8 | | 60x-153=9x | | 0.05(n+10)=0.95 | | 12r+17r= | | ((5x+10)+1)=4x | | 4c-7=37 | | -25-11x=-6x | | -12=9+-7x |